Distributions and controlling processes of the carbonate system in the Eastern Indian Ocean during autumn and spring - Wu, Xi; Yuan, Xiaolong; Liu, Xiaoqing; Wang, Xingzhou; Chen, Zhuo; Gu, Ting; Zhang, Guicheng; Gong, Xun; Sun, Jun (Frontiers in Marine Science, 2024)
The Eastern Indian Ocean (EIO) is an ideal region to explore the variability and controlling mechanisms of the seawater carbonate system and their potential influence on global climate change due to the distinctive environmental features, while studies in the EIO is far from sufficient. The spatiotemporal distributions of pH, dissolved inorganic carbon (DIC), alkalinity (Alk), and partial pressure of carbon dioxide (pCO2) were investigated in the EIO during autumn 2020 and spring 2021. The respective quantitative contributions of different controlling processes to DIC were further delineated. Significant seasonal variations were observed in the study area. Overall, the surface pH was lower and DIC, Alk, and pCO2 were higher during spring 2021 than during autumn 2020. The pH generally decreased from east to west during autumn 2020, whereas it decreased from north to south during spring 2021. The low values of DIC and Alk that were detected in the Bay of Bengal in these two seasons were mainly attributed to the influence of river inputs. Coastal upwelling during monsoon periods led to higher pCO2 and DIC values near Sumatra and Sri Lanka during spring 2021. The relationships of carbonate system parameters with different types of nutrients and different sized chlorophyll-a in the two seasons indicated the shifts of nutrients utilized by the phytoplankton, and phytoplankton species dominated the carbonate system variabilities. In vertical profiles, carbonate system parameters showed strong correlations with other physical and biogeochemical parameters, and these correlations were more robust during spring 2021 than during autumn 2020. The average sea–air flux of CO2 was 10.00 mmol m−2 d−1 during autumn 2020 and was 16.00 mmol m−2 d−1 during spring 2021, which revealed that the EIO served as a CO2 source during the study period. In addition, the separation of different controlling processes of DIC indicated stronger mixing processes, less CaCO3 precipitation, more intensive sea–air exchange, and weaker photosynthesis during spring 2021 than during autumn 2020.